Development and psychometric evaluation of the Employee's Workplace Cyberloafing Scale (EWCS) - Harlina Nurtjahjanti; Rahmat Hidayat; Indrayanti Indrayanti (Heliyon)
Cyberloafing refers to the practice of employees using the Internet for non-work-related purposes during working hours. This study aims to develop a measurement scale for cyberloafing among employees, specifically those working in Indonesia. The research was conducted in two stages. In the first stage, items were developed through a literature review, theme selection using qualitative research, expert review, and item readability testing. The results from this stage were then used in the second stage, which involved psychometric testing of the instruments using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). A total of 726 administrative employees from seven state universities in a major city on Java Island, Indonesia, participated in the study. The EFA test, conducted on 300 respondents, revealed a four-factor structure consistent with the construct. Subsequently, CFA was performed on 426 respondents, confirming the model's adequacy with four factors: entertainment, interaction, transaction, and recreation. The EFA results, validated by the CFA test, indicated that these factors accounted for 45.98 % of entertainment, 9.40 % of interaction, 6.36 % of transactions, and 5.15 % of recreation in cyberloafing behavior. The findings demonstrate that the Employee Workplace Cyberloafing Scale (EWCS) is a valid and reliable instrument for assessing cyberloafing among Indonesian workers. The EWCS serves as a versatile tool for both government and private sectors, providing critical insights into personal internet usage during work hours. Beyond mere monitoring, it reveals patterns indicative of addictive online behavior, empowering organizations to develop tailored intervention programs that address and mitigate employee mental health challenges.